Плоские модули и дистрибутивные кольца - Туганбаев, А.А. (Український математичний журнал, 1993)
Let A be a semi-primary ring entire over its center. We prove that the following conditions are equivalent: a) A is a ring distributive from the left (right), b) w. gl. dim (A) ≤ 1. In addition, if M is an arbitrary primary ideal of the ring A, A\M is a right Ore set.